The investigation of delay-constrained multicasting with minimum-energy consumption in static ad hoc wireless networks. (9th April 2009) - Yang, Wen-Lin; Wang, Lung-Jen
In this paper, we focus on the problem concerning how to construct a delay-constrained multicast tree with minimum-energy consumption in ad-hoc wireless networks. Based on link-replacing strategies, an algorithm called Energy-based Link Replacement (ELR) is presented. The ELR algorithm begins with a two-level multicast tree and then iteratively replaces the high-power links with a few of lower-power links in order to reduce the total power expended by the multicast tree. Unlike the prior approaches, the ELR can compute desired multicast trees directly. The simulation results show that our ELR outperforms the previously published method in terms of solution-quality and efficiency.